Regulation of Mutant p53 Protein Expression - Vijayakumaran, Reshma; Tan, Kah Hin; Miranda, Panimaya Jeffreena; Haupt, Sue; Haupt, Ygal (Frontiers in Oncology, 2015)
For several decades p53 has been detected in cancer biopsies by virtue of its high protein expression level and considered indicative of mutation. Surprisingly, however, mouse genetic studies revealed that mutant p53 is inherently labile, similar to its wild type counterpart. Consistently, in response to stress conditions, both wt and mutant p53 accumulate in the cell. While wt p53 returns to basal level following recovery from stress, mutant p53 remains stable. In part, this can be explained in mutant p53 expressing cells by the lack of an auto-regulatory loop with Mdm2 and other negative regulators, which are pivotal for wt p53 regulation. Further, additional protective mechanisms are acquired by mutant p53, largely mediated by the co-chaperones and their paralogs stress-induced heat shock proteins. Consequently, mutant p53 is accumulated in cancer cells in response to chronic stress and this accumulation is critical for its oncogenic gain of functions (GOF). Building on the extensive knowledge regarding wt p53, the regulation of mutant p53 is unravelling. In this review, we describe the current understanding on the major levels at which mutant p53 is regulated. These include the regulation of p53 protein level by microRNA and by enzymes controlling p53 proteasomal degradation.